2020
DOI: 10.1155/2020/1643015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis, Efficacy, and Safety of Antimalarial Hybrid Drug Comprising of Sarcosine and Aniline Pharmacophores as Scaffolds

Abstract: Malaria is a disease caused by protozoans transmitted to humans by infected female Anopheles mosquitoes. According to the WHO report of 2015, there were 214 million cases of malaria with 438,000 deaths worldwide. Ninety percent of world’s malaria cases occur in Africa, where the disease is recognized as a serious impediment to economic and social development. Despite advancement in malaria research, the disease continues to be a global problem, especially in developing countries. Currently, there is no effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Accordingly, the most potent among the tested natural compounds is galangin, followed by diosmin and piperine (Figure 2c). Based on the classification by WHO (Niyibizi et al 2020), galangin and diosmin are cytotoxic (IC 50 <90 µg/mL), while piperine is not (IC 50 >90 µg/mL). Taken together, galangin is the most promising chemoprevention agent among the three tested natural compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the most potent among the tested natural compounds is galangin, followed by diosmin and piperine (Figure 2c). Based on the classification by WHO (Niyibizi et al 2020), galangin and diosmin are cytotoxic (IC 50 <90 µg/mL), while piperine is not (IC 50 >90 µg/mL). Taken together, galangin is the most promising chemoprevention agent among the three tested natural compounds.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted, PGV-1 showed a remarkable cytotoxic activity with an IC 50 of 0.08 µM (Figure 2a). Among the tested natural compounds galangin exhibited the strongest cytotoxicity at IC 50 of 26 µM, followed by diosmin and piperine, 133 µM and 603 µM, indicating moderate cytotoxicity and not cytotoxic, respectively (Figure 2b, Table 1), based on cytotoxicity classification by World Health Organization (WHO) (Niyibizi et al 2020).…”
Section: Cytotoxicity Of Pgv-1 Diosmin Galangin and Piperine In Widr ...mentioning
confidence: 99%
“…It is found that the magnetic moment of these complexes (1.88 B.M.) is within the permissible range for the d 9 -system with a single unpaired electron [38,39].…”
Section: Magnetic and Electronic Spectral Studiesmentioning
confidence: 99%
“…For biochemical assays, the microtechnique was modified to a semiautomatic tritiated hypoxanthine incorporation assay, measuring Plasmodium uptake of radiolabelled hypoxanthine, a nucleic acid precursor, to assess the growth inhibitory effect of anti-malarial drugs [ 19 ] or immune serum [ 20 ]. Given a rapid, more precise and quantitative method, many recent reports have been adopted for the assessment of Plasmodium growth inhibition in experiments [ 21 ] and in a clinical trial setting [ 22 ] and for surveillance of drug resistance in field isolates [ 23 ]. In addition to DNA synthesis-based assays, Plasmodium parasites in intraerythrocytic stages also actively synthesize cell membranes composed of phospholipids; thus, an assay based on incorporation of the radioisotope-labeled phospholipid precursor ethanolamine was developed [ 24 ], allowing an assessment of anti-malarial compounds targeting enzyme functioning in fatty acid biosynthesis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%